Effects of clarified açai (Euterpe oleracea Mart) supplementation on oxidative stress markers in hemodialysis patients: A randomized, controlled pilot study - Isabelle Christine Vieira da Silva Martins; Denise Mafra; Hervé Rogez; Maria Conceição Nascimento Pinheiro; Keuri Eleutério Rodrigues; Barbarella de Matos Macchi; Andréa Dias Reis; Bruna Regis Paiva; Jessyca Sousa de Brito; Greicielle Santos da Silva; Abner Ariel da Silva Lima; Luís Claúdio Santos Pinto; et al. (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
Introduction: Patients with Chronic Kidney Disease (CKD) on Hemodialysis (HD) present a reduction of antioxidant enzymes levels and increased production of free radicals. Nutritional strategies have been used to mitigate the this exacerbatedoxidative stress in these patients and supplementation with açai (Amazon fruit Euterpe oleracea) can be a good candidate to exert a protective effect against oxidative stress. The aim of this pilot study was to evaluate the effects of açai supplementation on oxidative stress markers in patients with CKD on HD.  Methods: Eighteen patients were randomized to receive 20 mL of clarified açai pulp juice three times a week for eight weeks (8 patients, 55.5 ± 4.9 years; BMI, 24.8 ± 2.5 Kg/m2) and to be the control group who did not receive any supplementation (10 patients, 56.1 ± 3.4 years, BMI, 25.2 ± 0.7 Kg/m2). Oxidative stress markers plasma levels such as Malondialdehyde (MDA), nitrite, Total Glutathione (TG), Catalase (CAT) and Glutathione Peroxidase (GPx) were evaluated before and after supplementation.  Results: MDA plasma levels were significant reduced from 6.8 ± 1.2 to 5.8 ± 0.9 nmol/mL in açai group (p= 0.037), compared to no significant change in control group. The GSH total level presented slight increase after supplementation in açai group (320.7 ± 59.2 to 492.7 ± 84.8 nmol/mL, p=0.085). For Nitrite, CAT and GPx activity after eight weeks of supplementation with clarified açai (Euterpe oleracea Mart.) pulp there was no change.  Conclusion: The consumption of clarified açai for eight weeks improved lipid peroxidation in HD patients. This result suggests the promising application of açai as an antioxidant food to patients with CKD on HD.